(3QSGdI aj Lgd ONhd GdYGe GdYQHis - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO dGbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg hHYO CjgG GdCHf EPG CQOJ (B( (3GdeYQaI HCi jhe jONd GdeMQe aGWQM Sfi GdgLQI cdgG dZjQ YGec GdPi CQOJ eYQaJg HeGFJjf hYTQI s
(3BNQgG (B:s
(3RGd GdZHGQ Yf eSCdI eONd GdYGe GdYQHi LRi Gddg Yfg eTGjNfG NjQkG GfJgi HChGNQ ThGd YGe (B1278 (3g` s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs